دراسة مقارنة بين البنوك التقليدية والإسلامية، في تطبيق النظم والمعايير الاحترازية -بنك الفلاحة والتنمية الريفية وبنك البركة -: A comparative study between conventional and Islamic banks, in the application of precautionary systems and standards - Bank of Agriculture and Rural Development and Al Baraka Bank - - حابي عبد اللطيف,; حدوش شروق,; توينار رمضان, (Journal of North African Economies, 2025)
This study aims to know the extent to which traditional banks apply the Basel Conventions compared to the Islamic banks operating in Algeria, and the most important obstacles that limit the application of the axes of the agreement. Compared with traditional banks, however, this does not fully reflect the financial condition of the Islamic bank. As for the liquidity ratios, we find that the Islamic bank maintains much greater liquidity ratios compared to the traditional bank, and this is what makes it freeze its funds in order to cover the shortfall in paying sudden withdrawals, and it can be said that One of the most important factors for the failures that Islamic banks may face is the lack of a supportive legal, legislative and supervisory environment that operates in the same legal and legislative environment with traditional banks.